Optimizing screw shredder rotations for efficient shrubby tree branch processing - Ulashov Jonibek; Ivanov Timur; Toshmirzayev Murodilla; Karshieva Bogdagul; Khakimov Orifjon; Choriev Bekzod (EPJ Web of Conferences)
The volume of trees and branches grown in Uzbekistan is increasing year by year. Foreign experiences on processing and use of antlers are analyzed. According to the analysis, it became known that in recent years the volume of bushy tree branches in our republic has increased by 2-3 times, and there is a need to prepare and use various products from the branches. Taking this into account, in our country, creation of the bushy tree branch crushing apparatus, one of the crucial jobs is the construction plan and the technological work method. Based on this, the number of rotations of the screw of the crushing device was studied. Researches were carried out by changing the number of revolutions of the screw or auger of the grinding machine from 800 r/min to 1200 r/min. When the number of revolutions of the grinding screw is 1000 r/min, the amount of small fractions in the content of crushed branches and the smallest amount of indestructibility was achieved, and it was found that the quality of crushing branches has an acceptable value.